An exploratory study into teaching for social responsibility in apparel and textiles university programs - Sadtler, Grit (Kansas State University, 2022)
The purpose of this research was to investigate social responsibility in the apparel and textiles field through the lens of the faculty, including how they define social responsibility and incorporate it into the curriculum. This research explored how faculty who identify as teaching from a social responsibility perspective interpret the term, curriculum topics they address, their pedagogical approaches to instructional design of this curriculum, and the ways they assess student learning. As part of this research an interdisciplinary body of literature was examined within the context of teaching for social responsibility. Education was found to play a major role in encouraging young designers and industry professionals to embrace social responsibility, sustainable fashion, and to consider the product lifecycle (Moorhouse & Moorhouse, 2017). The quantitative research design for this study used a survey method. Analysis included frequency distributions, percentage ratios, and inductive analysis for the open-ended question data. This study aimed to improve the understanding for why and how apparel and textiles instructors include social responsibility in their curriculum. The findings showed that apparel and textiles instructors perceived social responsibility topics as important to the curriculum and that their personal experiences and beliefs influence how they define social responsibility. In addition, the results produced an updated and more inclusive list of social responsibility topics relevant to the current state of the apparel and textiles field. The results provided information about which instructional methods and assessment measures faculty use in their courses when teaching social responsibility topics. The findings aid in supporting faculty to include social responsibility in their teaching. Lastly, the results from this study can inform strategies to develop future curriculum design.
Keywords: Social responsibility; Apparel and textiles; Higher education; Critical pedagogy; Critical theory; Social change